Variation, contact, and reconstruction in the ancient Indo-European languages between linguistics and philology - Romagno, Domenica 1977-; Rovai, Francesco; Bianconi, Michele 1991-; Capano, Marta (Brill, 2022)
"The collected papers in this book address an array of important issues in the field of Historical Linguistics and, specifically, Indo-European Linguistics, including different theoretical approaches and innovative methodologies for studying language organization and change, building on the strict relationship between Linguistics and Philology. The papers provide significant contributions to the understanding of aspects of variation, contact and reconstruction, reflect a wide range of perspectives, and focus on issues and data from a large variety of languages. The themes that emerge from the papers center around two main research lines: 1. the relationship between language facts and historical accidents; 2. the relationship between grammatical categories and conceptual representations. The book is of interest for any reader seeking to gain insight into the nature of language organization and change"
Keywords: Indogermanische Sprachen; Sprachvariante; Sprachkontakt; Indo-European languages / Congresses; Languages in contact / Congresses; Language variation / Congresses; Reconstruction (Linguistics) / Congresses; Extinct languages / Congresses; Conference papers and proceedings; Konferenzschrift